Advancing the use of high-performance graphene-based multimodal polymer nanocomposite at scale - Ahmad, Ibrahim A.; Koziol, Krzysztof K.; Deveci, Suleyman; Kim, Hyun-Kyung; Kumar, Ramachandran Vasant (MDPI, 2018)
The production of an innovative, high-performance graphene-based polymer nanocomposite using cost-effective techniques was pursued in this study. Well-dispersed and uniformly distributed graphene platelets within a polymer matrix, with strong interfacial bonding between the platelets and the matrix, provided an optimal nanocomposite system for industrial interest. This study reports on the reinforcement of high molecular weight multimodal-high-density polyethylene reinforced by a microwave-induced plasma graphene, using melt intercalation. The tailored process included designing a suitable screw configuration, paired with coordinating extruder conditions and blending techniques. This enabled the polymer to sufficiently degrade, predominantly through thermomechanical-degradation, as well as thermo-oxidative degradation, which subsequently created a suitable medium for the graphene sheets to disperse readily and distribute evenly within the polymer matrix. Different microscopy techniques were employed to prove the effectiveness. This was then qualitatively assessed by Raman spectroscopy, X-ray diffraction, rheology, mechanical testing, density measurements, thermal expansion, and thermogravimetric analysis, confirming both the originality as well as the effectiveness of the process.
Keywords: Multimodal-high density polyethylene; Nanocomposite; Graphene; Melt extrusion; Polymer; Polymer degradation; Dispersion and distribution of graphene